THE INFLUENCE OF CONSUMER CREDIT AND INVESTMENT ON BANKING PROFITABILITY: CASE STUDY OF PT. BANK NEGARA INDONESIA (PERSERO) TBK MAMUJU BRANCH - haeruddin; Salijah, Erni (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This study aims to evaluate the partial influence of consumer credit and investment credit on profitability and the simultaneous influence of consumer credit and investment credit on profitability. This research uses a quantitative descriptive approach using quantitative data sourced from secondary data, namely the financial reports of PT. Bank BNI Mamuju Branch. The analysis used to test the hypothesis uses multiple linear regression analysis with the T test and F test. The findings from this study are that partially consumer credit has a positive effect on profitability and investment credit has a positive effect on profitability. Meanwhile, in simultaneous testing, the results showed that consumer credit and investment credit together had a significant effect on profitability.